Pseudo-Bartter syndrome in an infant with congenital chloride diarrhoea - Igrutinović Zoran (Srpski Arhiv za Celokupno Lekarstvo, 2011)
Introduction. Pseudo-Bartter syndrome encompasses a heterogenous group of disorders similar to Bartter syndrome. We are presenting an infant with pseudo-Bartter syndrome caused by congenital chloride diarrhoea. Case Outline. A male newborn born in the 37th gestational week (GW) to young healthy and non-consanguineous parents. In the 35th GW a polyhydramnios with bowel dilatation was verified by ultrasonography. After birth he manifested several episodes of hyponatremic dehydration with hypochloraemia, hypokalaemia and metabolic alkalosis, so as Bartter syndrome was suspected treatment with indomethacin, spironolactone and additional intake of NaCl was initiated. However, this therapy gave no results, so that at age six months he was rehospitalized under the features of persistent watery diarrhoea, vomiting, dehydration and acute renal failure (serum creatinine 123 μmol/L). The laboratory results showed hyponatraemia (123 mmol/L), hypokalaemia (3.1 mmol/L), severe hypochloraemia (43 mmol/L), alcalosis (blood pH 7.64, bicarbonate 50.6 mmol/L), high plasma renin (20.6 ng/ml) and aldosterone (232.9 ng/ml), but a low urinary chloride concentration (2.1 mmol/L). Based on these findings, as well as the stool chloride concentration of 110 mmol/L, the patient was diagnosed congenital chloride diarrhoea. In further course, the patient was treated by intensive fluid, sodium and potassium supplementation which resulted in the normalization of serum electrolytes, renal function, as well as his mental and physical development during 10 months of follow-up. Conclusion. Persistent watery diarrhoea with a high concentration of chloride in stool is the key finding in the differentiation of congenital chloride diarrhoea from Bartter syndrome. The treatment of congenital chloride diarrhoea consists primarily of adequate water and electrolytes replacement.